JOM FMIPA Volume 1 No. 2 Oktober 291 PERTUMBUHAN CACING TANAH (Perionyx sp) PADA DUA MEDIA - Rotupa Juliana Manurung; Yusfiati '; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This research was conducted to determine the growth of earthworm ( Peryonix sp) in two types of media, that is mixture of palm sheath waste with chicken manures and mixture of vegetables waste with chicken manures. This research was conducted at Biological Garden Department of Biology Math and Science Faculty Riau University. The research used completely randomized design with five treatments and three replications i.e treatments M1 (100% palm sheath waste); M2 (75% palm sheath waste + 25% chicken manure); M3 (50% palm sheath waste + 50% chicken manure); M4 (25% palm sheath waste + 75% chicken manure) and M5 (100% chicken manure), S1 (100% vegetables waste); S2 (75% vegetables waste + 25% chicken manure); S3 (50% vegetables waste + 50% chicken manure); S4 (25% vegetables waste + 75% chicken manure) and S5 (100% chicken manure). Analysis of variance showed that type of media had significantly affected body weight and amount of coccon produced. The biggest body weight and amount coccon were at media M2 and S3 in the day of 20.